Hakulausekkeen muodostamisen vaikeus – nuorten ja opettajien taidot testissä - Loretta Saikkonen (Finland, 2022)
The research objective was to find out Finnish 12–22-year-old students' (N=3222) and primary, secondary and high school teachers' (N=573) information retrieval skills in forming a search phrase and using search operators. The results indicate that the skills for defining search queries among youths and teachers are insufficient. Teachers performed better in forming a search phrase than the students, even though high school students succeeded better than over 45-year-old teachers. Male teachers performed significantly better in forming a search phrase than female teachers. Half of the teachers and a fifth of the students used search operators in their search phrases. Overall, the search phrases created by the students and teachers were too simple and did not cover the entire assignment. Every tenth of the students tried to create a web address instead of a search phrase and some students wrote requests or questions to the search engine.
On the basis of these students' mistakes in the search phrase task, one can state that students need more training especially on forming comprehensive search phrases, using typical search operators, and understanding the functions of search engines.